Analysis of the correlation between youth-developing provinces and common wealth—Taking Zhejiang Province as an example - Li Jieyu; Zhao Qing (SHS Web of Conferences, 2024)
Youth development province refers to the province development method that mutually stimulates youth innovation and creative vitality and province innovation and creative vitality, and mutually promotes youth high-quality development and province high-quality development. 2021 The Opinions of the Central Committee of the Communist Party of China and the State Council on Supporting the High-quality Development of Zhejiang Province to Construct a Common Wealth Demonstration Zone, which was introduced in 2021, further clarifies that the judgment indicators for the realization of the common wealth can be classified into 10 aspects, namely high-quality development, Income Distribution, Social Public Services, Resident Income, Quality of Life, Culture and Entertainment, Basic Education, Sustainable Ecology, Life Safety, Information and Transportation. Taking Zhejiang Province as an example, this paper starts from the question of whether there is a certain correlation between the building of youth development province and the realization of common prosperity, and analyzes the correlation between the index of youth development province and the index of common prosperity in Zhejiang Province, and discusses and expounds the construction direction of the goal of “common prosperity” in Zhejiang Province.